Medizin dient der Gesundheit, Informatik der Daseinsgestaltung – Synergie in Dualität: Über das erste halbe Jahrhundert Medizinische Informatik Heidelberg/Heilbronn. - Haux, Reinhold (GMS Medizinische Informatik, Biometrie und Epidemiologie, 2024)
The Heidelberg-Heilbronn medical informatics program, whose foundation and development during its first 50 years are reported here, was initially established in 1972 as a diploma program, then converted into a consecutive bachelor's and master's program starting in 2007. With approximately 2,000 graduates, it is probably not only the world's oldest dedicated medical informatics program, but also the one with the most graduates. Important impulses have been set nationally and internationally by teachers as well as by graduates of the Heidelberg-Heilbronn medical informatics program. An important piece of history was written at Heidelberg University and Heilbronn University of Applied Sciences with this medical informatics program. In terms of its objectives, the field of medical informatics belongs to medicine. In terms of methods and tools, it can be largely assigned to computer science. To adequately map the synergies that can arise from this duality of medicine and informatics in a dedicated medical informatics curriculum was and remains an important as well as challenging task.